Learning e-portfolio: reconciling constructivist portfolios with positivist portfolios in response to outcome-based approach to learning - Mat Daud, Nuraihan (IIUM Press and IPPTN, 2009)
Introduction: In the Malaysian National Higher Education Strategic Plan and National Higher Education Action Plan 2007-2010, seven thrusts are identified and these include: widening access and enhancing quality; improving the quality of teaching and learning; enhancing research and innovation; strengthening higher learning institutions; intensifying internationalisation; enculturation of lifelong learning; and reinforcing the ministry's delivery system. Many commended the plan for the bold move to transform the landscape of tertiary education in Malaysia (Chapman et aI., 2007).